CD40/CD154 blockade inhibits dendritic cell expression of inflammatory cytokines but not costimulatory molecules. - Ferrer, I; Liu, D; Pinelli, D; Koehn, B; Stempora, L; Ford, M (2012)
Blockade of the CD40/CD154 pathway remains one of the most effective means of promoting graft survival following transplantation. However, the effects of CD40/CD154 antagonism on dendritic cell (DC) phenotype and functionality following transplantation remain incompletely understood. To dissect the effects of CD154/CD40 blockade on DC activation in vivo, we generated hematopoietic chimeras in mice that expressed a surrogate minor Ag (OVA). Adoptive transfer of OVA-specific CD4(+) and CD8(+) T cells led to chimerism rejection, which was inhibited by treatment with CD154 blockade. Surprisingly, CD154 antagonism did not alter the expression of MHC and costimulatory molecules on CD11c(+) DCs compared with untreated controls. However, DCs isolated from anti-CD154-treated animals exhibited a significant reduction in inflammatory cytokine secretion. Combined blockade of inflammatory cytokines IL-6 and IL-12p40 attenuated the expansion of Ag-specific CD4(+) and CD8(+) T cells and transiently inhibited the rejection of OVA-expressing cells. These results suggest that a major effect of CD154 antagonism in vivo is an impairment in the provision of signal three during donor-reactive T cell programming, as opposed to an impact on the provision of signal two. We conclude that therapies designed to target inflammatory cytokines during donor-reactive T cell activation may be beneficial in attenuating these responses and prolonging graft survival.